1997
DOI: 10.2486/indhealth.35.61
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of a Low Level of Indium Phosphide (InP) in Rats after Intratracheal Instillation.

Abstract: To clarify the instillation toxicity of low level of indium phosphide (InP), 0, 1.2, 6.0 and 62.0 pg/kg body weight of InP particles were instilled intratracheally in male Fischer 344 rats, and the effects of InP were examined on the following day (day 1) and on the 8th day (day 8) after instillation. Indium was measured but not detected in the serum, liver, kidney, spleen, thymus and brain. Dose-related mild elevation of superoxide dismutase (SOD) activity and lactate dehydrogenase (LDH) activity in bronchoal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0
2

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 19 publications
0
10
0
2
Order By: Relevance
“…From the mid-1990s, animal experiments have shown that the inhalation or intratracheal instillation of In compounds causes severe lung inflammation [1][2][3][4][5][6][7] and mild adverse reproductive effects [8][9][10] . Although the health effects of In on workers' respiratory and reproductive systems have been unclear to date, assessing the exposure-effect relationships in Inexposed workers is a serious concern, but no information is available on the exposure-effect relationships in workers.…”
mentioning
confidence: 99%
“…From the mid-1990s, animal experiments have shown that the inhalation or intratracheal instillation of In compounds causes severe lung inflammation [1][2][3][4][5][6][7] and mild adverse reproductive effects [8][9][10] . Although the health effects of In on workers' respiratory and reproductive systems have been unclear to date, assessing the exposure-effect relationships in Inexposed workers is a serious concern, but no information is available on the exposure-effect relationships in workers.…”
mentioning
confidence: 99%
“…Due to the increasing production of ITO, the potential health hazards of occupational or environmental exposure to this material have began to cause great concern. Since the mid 1990's, data have become available indicating that indium compounds can be toxic to animals [2][3][4][5][6][7][8][9][10][11][12] , although there is little information regarding the adverse health effects for workers exposed to indium compounds. In 2003, the first case of interstitial pneumonia caused by occupational exposure to ITO was reported 13) .…”
mentioning
confidence: 99%
“…It presents also a direct bandgap, making it useful for optoelectronics, biomedical devices and for fluorescence applications as QDs. Unfortunately, a high toxicity of the InP has been reported [14,15], thus rendering the InP surfaces biocompatible is a crucial issue.…”
Section: Introductionmentioning
confidence: 99%